Systolic Compression of Intramural Coronary Arteries in Hypertrophic Cardiomyopathy - Muhammet Rasit Sayin; Sait Mesut Dogan; Turgut Karabag; Ibrahim Akpinar; Mustafa Aydin (Case Reports in Cardiology)
We report a case of hypertrophic cardiomyopathy due to systolic total narrowing of side branches of all major coronary arteries.